Adolescents hospitalised for suicidality: biomarkers, social and affective predictors: a cohort study. Issue 10 (3rd October 2022) - Nugent, Nicole R; Armey, Michael; Boker, Steven; Brick, Leslie; Knopik, Valerie; McGeary, John E; Spirito, Anthony; Mehl, Matthias R
Abstract : Objectives: The present research examines genomics and in vivo dynamics of family context and experienced affect following discharge from psychiatric hospitalisation for suicidal thoughts and behaviours (STBs). The purpose of this paper is to provide an overview of a new model, description of model-guided integration of multiple methods, documentation of feasibility of recruitment and retention and a description of baseline sample characteristics. Design: The research involved a longitudinal, multimethod observational investigation. Setting: Participants were recruited from an inpatient child and adolescent psychiatric hospital. 194 participants ages 13–18 were recruited following hospitalisation for STB. Primary and secondary outcome measures: Participants underwent a battery of clinical interviews, self-report assessments and venipuncture. On discharge, participants were provided with a phone with (1) the electronically activated recorder (EAR), permitting acoustic capture later coded for social context, and (2) ecological momentary assessment, permitting assessment of in vivo experienced affect and STB. Participants agreed to follow-ups at 3 weeks and 6 months. Results: A total of 71.1% of approached patients consented to participation. Participants reported diversity in gender identity (11.6% reported transgender or other gender identity) and sexual orientation (47.6% reported heterosexual or straight sexual orientation). Clinical interviews supported a range of diagnoses with the largest proportion of participants meeting criteria for major depressive disorder (76.9%). History of trauma/maltreatment was prevalent. Enrolment rates and participant characteristics were similar to other observational studies. Conclusions: The research protocol characterises in vivo, real-world experienced affect and observed family context as associated with STB in adolescents during the high-risk weeks post discharge, merging multiple fields of study.